The Efficacy of Using Comics Strips in Reading Class at MA Ma'arif Roudlotut Tholibin: English - Irma Triana; Wiwed Pratiwi; Rizky Hidayatullah (Journal of English Development, 2023)
This study aims to determine whether using comic strips in instructional activities improves students' reading comprehension, particularly when it comes to narrative texts. This study employed a quasi-experimental design in a quantitative manner. Students from MA Ma'arif Roudlotuth Tholibin, with two sample classes of 20 students each, made up the study's population. There was an experimental class and a control class assigned to both classes. The pre- and post-test methods were used to gather the data. The computation in this study indicated that comic strips are a useful teaching and learning tool for narrative text. The experimental class's mean post-test score, which was 70.40 while the control class's score was 68.17, confirmed this conclusion. This suggests that the post-test mean for the experiment class (70.40>68.17) was higher than the control class's. As a result, the statistics showed that 1.937 > 1.67= tobserve > ttable, proving that The Alternative Hypothesis (Ha) is accepted and the Null Hypothesis is rejected.. In conclusion, using comic strips to instruct students in reading comprehension of narrative texts is an effective strategy to raise their reading skill.